Revocation of islamic inheritance rights to the recipient of the obligatory will perspective maslahah - Hasbi, Mhd (Legalpreneur Journal, 2026)
This study examines the issue of the cancellation of Islamic inheritance rights to the recipient of the obligatory will which is analyzed through the perspective of maslahah. The background of this study is the limitation of the regulation of mandatory wills in the compilation of Islamic law (KHI), especially Article 209, which does not explicitly regulate the mechanism for their cancellation, causing legal uncertainty in judicial practice. This research uses normative juridical method with conceptual approach and legislation. The results showed: first, the cancellation of the rights of the obligatory will can only be justified if it is based on causes recognized by the Shari'a, such as harming the heir or obstructive religious differences; second, the perspective of maslahah considers the cancellation to be legally valid if it aims to preserve greater benefits, but prohibited if it is carried out discriminatively; third, the absence of detailed arrangements on the mechanism for canceling the obligatory will in the KHI implies the weak protection of the recipient's civil rights. This study recommends a comprehensive renewal of the KHI in order to realize legal certainty and substantive justice in the Islamic inheritance system in Indonesia.